Contemporary theories about the family - Hill, Reuben; Burr, Wesley (New York: The Free Press, 1979)
Contents : Choice, exchange, and the family,simbolic interaction and the family,the general systems approach to the family,conflict theory and the study of marriage and the family,toward a phenomenological sociology of family : a programmatic essay.
Includes bibliographical references and index
Keywords: Familia - Sociología Familiar